The Effect of Solvent on the Characteristics of FeBTC MOF as a Potential Heterogenous Catalyst Prepared via Green Mechanochemical Process - Yati, Indri; Ridwan, Muhammad; Padella, Franco; Pentimalli, Marzia (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
In this study, the synthesis of FeBTC (BTC = 1,3,5-benzenetricarboxylate) also known as MIL-100 (Fe) metal organic framework (MOF) has been carried out successfully using green mechanochemical method (neat grinding and liquid assisted grinding). The effect of solvent used in the synthesis was investigated for the first time to elucidate the physicochemical properties of FeBTC including crystal structure, thermal stability, pore size and specific surface area. The physicochemical properties of all FeBTC obtained in this study were compared to commercial FeBTC (Basolite F-300), characterized using powder X-Ray Diffraction (XRD), Thermogravimetric Analysis (TGA) and nitrogen physisorption isotherms. All Fe-BTC MOF synthesized in this study showed improved textural properties compared to commercial Basolite F-300 such as higher crystallinity, higher surface area and larger pore size. It was found that the best synthesis method was by using the mixture of ethanol and water with equal volume ratio as solvent. The highest BET surface area of FeBTC synthesized using this method was 972 m2/g for FeBTC-EtOH/H2O. This value is 2.3 times higher than the surface area of commercial Basolite F-300 (418 m2/g). FeBTC with higher surface area is expected to have higher catalytic activity which makes this FeBTC an excellent candidate as a heterogenous catalyst for many reactions such as aldol condensation or esterification reaction. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).